Development of a Tapak Suci Instructional Textbook for Junior High School Students - RamadhanNst, Billy; Alfiansyah Putra Karo, Alan; Puspa Sari, Liliana (Mamaos:Journal Physical Education, Sport and Art, 2025)
The need for structured and standardized learning materials in Tapak Suci martial arts has become increasingly urgent, especially at the junior high school level where instructional resources are often limited. This study aimed to develop and validate an illustrated instructional textbook to support systematic Tapak Suci learning. The ADDIE model was employed, covering analysis, design, development, implementation, and evaluation stages. Expert validation was conducted by a media specialist and a Tapak Suci material expert, while practicality testing involved 10 students. The media expert provided a score of 9/9 (100%), indicating excellent visual quality and usability. The material expert also assigned a score of 9/9 (100%), confirming content accuracy and alignment with Tapak Suci fundamentals. Practicality testing produced a 100% positive response, showing that students found the textbook easy to understand and suitable for skill practice. These results demonstrate that the developed textbook is highly valid and practical, supporting its feasibility for use in Tapak Suci instruction at junior high schools.